The Impacts of Implementation Accounting Standard PSAK No. 24 (Revision 2004) on Post Employment Benefit Towards Company’s Performance - Elfrida Yanti (Binus Business Review, 2011)
Financial analysis is useful for all company to measure their performance and expected to show improvement result in order to determine the company’s condition. . Financial ratios are tools to help anticipate the future conditions and to predict some actions or strategies that will useful in improving the company’s future performance, which is from evaluating the previous financial statement. Using financial ratios this research tries to impose one indicator, post employment benefit and how it would impact company financial performance. PT. ABC Will be the object case which implementation the post employment benefit based on particular regulation PSAK No. 24 (revision 2004). The researcher would like to focuses on the profitability ratios by Return on Asset ratio (ROA), liquidity ratio by Current Ratio (CR) and the leverage ratio by Debt-Equity ratio.